2020
DOI: 10.2147/ott.s235940
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inhibition of TRIM32 Induced by miR-519d Increases the Sensitivity of Colorectal Cancer Cells to Cisplatin</p>

Abstract: Background: Colorectal cancer is a leading cause of cancer-related death in the world. Despite cisplatin is a commonly used chemotherapeutic drug for the colorectal cancer treatment, resistance of cancer cells to cisplatin restricts its clinical efficacy. It is important to explore the potential mechanisms and take strategies to sensitize colorectal cancer cells to cisplatin treatment. Methods: Differences of TRIM32 and miR-519d expression between colorectal cancer cells and human normal colon epithelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Furthermore, miRNA-519d impedes CP resistance by inducing apoptosis through MCL-1-dependent mitochondrial pathway [93]. In colorectal cancer cells, miRNA-519d down-regulates the expression level of tripartite motif 32 (TRIM32) to enhance ROS levels, leading to mitochondrial dysfunction and increased CP sensitivity [94]. Investigating the expression level demonstrates that miRNAs with tumor-suppressing role undergo down-regulation in CP resistant-cancer cells.…”
Section: Ros Cisplatin Chemotherapy and Related Molecular Pathways Cisplatin Sensitivitymentioning
confidence: 99%
“…Furthermore, miRNA-519d impedes CP resistance by inducing apoptosis through MCL-1-dependent mitochondrial pathway [93]. In colorectal cancer cells, miRNA-519d down-regulates the expression level of tripartite motif 32 (TRIM32) to enhance ROS levels, leading to mitochondrial dysfunction and increased CP sensitivity [94]. Investigating the expression level demonstrates that miRNAs with tumor-suppressing role undergo down-regulation in CP resistant-cancer cells.…”
Section: Ros Cisplatin Chemotherapy and Related Molecular Pathways Cisplatin Sensitivitymentioning
confidence: 99%
“…It was reported that TRIM32 played a pro‐apoptotic role via destabilizing mitochondrial membrane potential and degradation of XIAP in normal cells 32,33 . In the context of cancer, TRIM32 was able to promote the proliferation and motility of lung, gastric, squamous cancer cells or contribute to cisplatin resistance in colorectal cancer, whereas the role of TRIM32 in PDAC cells remained unknown 34‐38 . In our study, we found that the combination treatment of ibr‐7 and gemcitabine could diminish TRIM32 at a transcriptional level, probably through enhancing the methylation status of TRIM32 (Figure 5F,G).…”
Section: Discussionmentioning
confidence: 61%
“…TRIM32 exerts a key role in regulating the survival and apoptosis of various cell types. TRIM32 can inhibit the apoptosis of cancer cells and enhances cell survival under exposure to chemotherapeutics [38][39][40].…”
Section: Discussionmentioning
confidence: 99%